2016
DOI: 10.1007/s13402-016-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Giganteaside D induces ROS-mediated apoptosis in human hepatocellular carcinoma cells through the MAPK pathway

Abstract: From our results we conclude that GD can induce ROS-mediated apoptosis in HCC-derived cells through the MAPK pathway. This observation may open up avenues to explore the future use of GD as a HCC chemotherapeutic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…As expected, SB202190 and SP600125 had no effect on the mRNA expression of the NOX subunits (P>0.05). These results are consistent with those of previous studies, which also indicated that increased ROS production may be abolished by NAc and apocynin (21,22).…”
Section: Effect Of Ethanol On Ros Generation In L-02 Cellssupporting
confidence: 94%
“…As expected, SB202190 and SP600125 had no effect on the mRNA expression of the NOX subunits (P>0.05). These results are consistent with those of previous studies, which also indicated that increased ROS production may be abolished by NAc and apocynin (21,22).…”
Section: Effect Of Ethanol On Ros Generation In L-02 Cellssupporting
confidence: 94%
“…The very poor prognosis and high recurrence rate of HCC is due to tumor invasiveness, frequent intrahepatic spread, and extrahepatic metastasis. Although numerous studies have demonstrated that a complex gene network is involved in the tumorigenesis and progression of HCC, the detailed regulatory mechanisms of key pathways remain obscure . Therefore, improvements in understanding the molecular processes involved in HCC could reveal new monitoring methods and treatment targets for improving HCC diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol intake can lead to overexpression of ROS, leading to oxidative stress and causing apoptosis [50,51]. SOD and GGT play an important role in oxidative stress, while bcl-2 and bax have a very important role in cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%